2021
DOI: 10.1186/s12929-021-00762-2
|View full text |Cite
|
Sign up to set email alerts
|

HBx facilitates ferroptosis in acute liver failure via EZH2 mediated SLC7A11 suppression

Abstract: Background Acute liver failure (ALF) is a syndrome of severe hepatocyte injury with high rate of mortality. Hepatitis B virus (HBV) infection is the major cause of ALF worldwide, however, the underlying mechanism by which HBV infection leads to ALF has not been fully disclosed. Methods D-GalN-induced hepatocyte injury model and LPS/D-GalN-induced ALF mice model were used to investigate the effects of HBV X protein (HBx) in vitro and in vivo, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 38 publications
5
42
0
Order By: Relevance
“…It has been reported that the ferroptosis caused by D-GalN/LPS is associated with organ injury. D-GalN/LPS-induced liver injury was accompanied with iron accumulation and ROS production, substances that regulate ferroptosis -related signaling in hepatocytes are expected to contribute to the treatment of D-GalN/LPS-induced ALI ( Liu et al, 2021 ; Siregar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the ferroptosis caused by D-GalN/LPS is associated with organ injury. D-GalN/LPS-induced liver injury was accompanied with iron accumulation and ROS production, substances that regulate ferroptosis -related signaling in hepatocytes are expected to contribute to the treatment of D-GalN/LPS-induced ALI ( Liu et al, 2021 ; Siregar et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…2 A). Based on the evidence that trimethylation of H3K27 causes gene silencing and transcriptional suppression [ 31 ], RIP assay was performed (Fig. 2 B), and the outcome suggested that LINC00114 was enriched in the immunoprecipitates under EZH2 and H3K27me3 antibody treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, SLC7A11 prevents cells from undergoing ferroptosis by importing cystine and promoting GSH synthesis. In acute liver failure, overexpression of SLC7A11 plays a protective role in controlling the level of lipopolysaccharide-D-galactosamine-induced hepatocyte acute injury primarily through inhibiting ferroptosis ( 72 ). In contrast, SLC7A11 enhances ferroptosis in myofibroblast hepatic stellate cells, which can exacerbate liver injury ( 73 ).…”
Section: The Functional Role Of Slc7a11 In Cellular Stress and Carcin...mentioning
confidence: 99%